Portfolio design for interiors - Linton, Harold; Engel, William (Artist) (New York Bloomsbury , Fairchild Books an imprint of Bloomsbury Publishing Inc, 2017)
"Portfolio Design for Interiors teaches the aspiring interior designer how to create a professional quality portfolio. Using real examples of outstanding student portfolios, authors Harold Linton and William Engel demonstrate how to analyze, organize, problem-solve, and convey diverse types of visual and text information in various forms of historic, contemporary, and innovative styles. The text features a robust art program and examples of various presentation applications, including graduate study, employment, scholarships, grants, competitions, and fellowships. This is an accessible and comprehensive resource for students learning professional portfolio design"--
2
Keywords: Design services -- Marketing; Interior decoration rendering